The Effect of Digital Literacy and Entrepreneurship Education Towards Online Entrepreneurship Intention Through Online Business Learning and Creativity At Marketing Department in Batang Regency - Mugiono, Mugiono; Dian Wisika Prajanti, Sucihatiningsih; Wahyono, Wahyono (Universitas Negeri Semarang, 2021)
The intention of online entrepreneurship is the desire of a person by making several efforts to find information and planning to achieve business goals in the internet network. Some of the factors that are thought to influence this phenomenon include digital literacy, entrepreneurship education, online business learning, and creativity. This study aims to analyze the effect of digital literacy, entrepreneurship education, online business learning, and creativity on online entrepreneurial intentions. In addition, this study is to analyze the effect of digital literacy and entrepreneurship education that can be mediated by online business learning and creativity on online entrepreneurial intentions of Marketing major in Batang regency. This research method was a quantitative approach. The population of this study were students majoring in Marketing in Batang with a total of 345 students. The sample taken in this study were 160 students as respondents by collecting data using a questionnaire. The data analysis method used was descriptive analysis, confirmatory analysis and structural equation modeling analysis. The results show that digital literacy and online business learning have a positive and significant effect on online entrepreneurship intentions. Meanwhile, entrepreneurship education and creativity have a negative and significant effect on online entrepreneurial intentions. However, entrepreneurship education has no effect on creativity. Online business learning variables and creativity mediate digital literacy towards online entrepreneurial intentions. While the creativity variable does not mediate entrepreneurship education on online entrepreneurship intentions. Based on the research results, Entrepreneurship Education has no influence on creativity. So the school needs to carry out entrepreneurial education activities that can increase the creativity of students.